Global orthopedics : caring for musculoskeletal conditions and injuries in Austere settings - Spiegel, David A.; Foltz, Michelle; Gosselin, Richard A. (Springer New York, 2014)
Global Orthopedics: Caring for Musculoskeletal Conditions and Injuries in Austere Settings was conceived and written to be a unique reference for surgeons working in resource-limited environments. The first sections provide historical background, global public health perspectives of orthopedics, the role of culture, and a broad discussion of non-surgical and non-orthopedic clinical topics that are rarely encountered in high-resource settings but that affect orthopedic care. Adult and pediatric trauma are presented in an anatomical format for easy reference, with a focus on the natural history and the best treatment methods within existing limitations. The chapters on musculoskeletal infections provide a wealth of knowledge about these common debilitating conditions that is unavailable in any other single modern text. The non-infectious pediatric conditions section has been written for the non-specialist to handle selected developmental and early childhood orthopedic problems commonly seen in low-resource settings. Detailed chapters on reconstruction surgery, tumor management, amputations, and the orthopedic needs in the face of conflicts and natural disasters round out the text.